Developing student-teachers attitude and mindset of a professional through school-based experience programme: an evaluation research approach - Mabade, Avhurengwi Samson; Ngobeni, Nyiko Condry (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study addresses the need for practical engagement of student-teachers in real classroom environments to bridge the gap between theoretical knowledge and practical application, thereby cultivating a professional attitude and mindset through the School-Based Experience (SBE) program. The research focuses on evaluating how immersive, hands-on teaching experiences within the SBE framework contribute to the holistic professional development of student-teachers, preparing them to meet the demands and challenges of the teaching profession effectively. The aim is to motivate schools to actively support student-teachers in this transformative journey. Professionalism, characterized by a moral commitment to action and a professional attitude in interactions, demands a principled standard of practice. While higher education institutions bear the responsibility of instilling these values, collaborative efforts involving stakeholders, especially schools, are pivotal. The study adopts an Evaluation Research Approach to assess the effectiveness of the SBE program in developing a professional mindset. Randomly selecting five schools and ten student-teachers, along with two teachers and mentors from each school, the researchers conducted interviews to gauge contributions towards fostering a professional mindset during the SBE program. The findings underscore the importance of theoretical and empirical knowledge, emphasizing the need for reciprocal relationships within schools. Trustworthiness and adherence to principled standards emerge as critical components. The study, with a total of twenty participants, presents their responses as an evaluation research report, demonstrating the significance of the SBE program in shaping the attitudes and mindsets of future professionals. This research sheds light on an underexplored aspect of developing professionalism in student teachers, contributing valuable insights to the educational landscape.